Factors Related with Knowledge of Basic Life Support among Members of Student Body Volunteer Organizations at Universitas Padjadjaran - Nur Fadilla; Irvan Afriandi; Rudi Herman Sitanggang; Elsa Pudji Setiawati (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Mortality caused by accidents remains a public health challenge. Prompt response during first aid accident may prevent disability or death. At Universitas Padjadjaran three student body volunteer organizations provide training in Basic Life Support as the component of first aid. They are Korps Sukarela Palang Merah Indonesia (KSR PMI), Perhimpunan Mahasiswa Pecinta Alam (PMPA) Palawa, and Unit Search and Rescue (SAR). This study aims to assess the level of Basic Life Support knowledge of the members inthree organizations and the factors related with their knowledge.Methods: The method used was a descriptive study carried out on subjects diagnosed with PSS at the National EThis was a cross sectional study that included 59 members of three student body volunteer organizations of Universitas Padjadjaran that have received training in Basic Life Support. A questionnaireabout respondent’s characteristics, Basic Life Support-related experiences, and Basic Life Support’s knowledge was administered to the participants during October 2012Results: The total mean for the three student body volunteer organizations on questionnaire was 64.12±19.40 with minimum score was 25 and maximum score was 100. The interval of last period of training and Basic Life Support-related experiences did not show statistically significant (p=0.647) and(p=0.357) however educational background related to Basic Life Support knowledge showed statistically significant (p<0.01).Conclusions: The level of Basic Life Support knowledge in three student body volunteer organizations was moderate and that educational background has relation with the knowledge. The increase in number of effective training and application in the field may increase the knowledge on Basic Life Support. [AMJ.2015;2(1):186–90]